Parasitoid larva-pupa Tetrastichus howardi (Hymenoptera: Eulophidae) pada Pluttella xylostella L. (Lepidoptera: Yponomeutidae) di pertanaman kubis kecamatan batu dan poncokusumo, kabupaten malang - Sri Karindah; Sutanto Sutanto; E. Siswanto; L. Sulistyowati (Perhimpunan Entomologi Indonesia, 2005)
The surveys of larval parasitiod Plutella xylostella, which have been done in cabbage plantations area in Batu and Poncokusumo, Malang east Java, found other larval parasitoid biside the commonly larval parasitiod Diagdema semiclausum. The parasitoid was Teratichus howardi (Hyminoptera: Eulophidae). The percentage of parasitism was dependent of the altitude of cabbage plantation and developmental stage of crop. The percent of parasitism could reach 82% when parasitized larvae sampled in cabbage plant and the crop stage. Parasitism was also higher at the medium lowland rather than it was that the upland. T. howardi is a gregrarious larval-pupa endoparasitoid. The life cycle of T. howardi was 14-16 days. The longevity of male and female was influenced by the availability of hosts or the change of mating. The longevity of mated female which was offered some host is 14-21 days, but the longevity of mated female without hosts was 38-56 days. The mated male parasitoid lived from 1 to 4 days, but they lived 12-16 days when they were not mated. One female could lay some cluster of egg varied from 35-60 eggs cluster or from 142 to 235 eggs during the lifespan. One eggs cluster consist of ±4 eggs. The parasitoid laid one or two clusters of egg per host. Parasitoid laid eggs soon after mating at day one from eclosion until day 19th. Four to 28 Parasitoids could emerge from one host. One parasitoid was able to parasitize 17-30 larvae of P. xylostella.